Use and Yield of Baseline Imaging and Laboratory Testing in Stage II Breast Cancer. (22nd August 2016) - Bychkovsky, Brittany L.; Guo, Hao; Sutton, Jazmine; Spring, Laura; Faig, Jennifer; Dagogo‐Jack, Ibiayi; Battelli, Chiara; Houlihan, Mary Jane; Yeh, Tsai‐Chu; Come, Steven E.; Lin, Nancy U.
Abstract : Background: Despite guideline recommendations, baseline laboratory testing and advanced imaging are widely ordered in clinical practice to stage asymptomatic patients with clinical stage II breast cancer (BC). Materials and Methods: A retrospective study at two academic centers in Boston, Massachusetts, between 2006 and 2007 explored the use, results, and implications of laboratory tests, tumor markers, and imaging in patients with clinical stage II BC. Results: Among 411 patients, 233 (57%) had liver function testing, 134 (33%) had tumor marker tests, and 237 (58%) had computed tomography (CT) as part of their initial diagnostic workup. Median age was 52 (range, 23–90 years). On multivariable analysis, young age, more advanced stage, and tumor subtype (human epidermal growth receptor‐positive [HER2+] and triple‐negative breast cancer [TNBC]) were significantly associated with baseline CT. The rate of detection of true metastatic disease with use of baseline staging imaging was 2.1% (95% confidence interval, 0.7%–5%). It was 2.2% (3 of 135) for estrogen receptor/progesterone receptor‐positive disease, 1.9% (1 of 54) for HER2+ disease, and 2.1% (1 of 48) for TNBC. At 5 years of follow‐up, 46 of 406 patients were diagnosed with metastatic breast cancer. Thirty‐four of 46 (73.9%) who developed recurrent disease had imaging at their initial diagnosis, and of these, five had abnormalities on their initial imaging that was correlated with where they developed metastatic disease. Conclusion: In this cohort of women with stage II BC, staging imaging at diagnosis had a low yield in detecting distant metastases (2.1%). The detection rate was not higher with HER2+ disease or TNBC, despite the trend that patients with these subtypes were more likely to undergo imaging. Implications for Practice: Despite guideline recommendations, asymptomatic patients with stage II breast cancer (BC) often undergo staging imaging with computed tomography, bone scanning, or positron emission tomography. Physicians have often reported that they order imaging despite recommendations because they believe that younger patients or patients with more aggressive BC phenotypes, such as human epidermal receptor 2‐positive BC or triple‐negative BC, benefit from staging imaging. In this cohort of women younger than those in prior studies, the yield of detecting distant metastatic disease in patients with clinical stage II BC was very low and the detection rate was not higher in the presence of HER2‐positive or triple‐negative BC. Abstract : This study suggests that liver function tests, tumor markers, and routine body imaging are unnecessary for the initial evaluation of asymptomatic women with stage II breast cancer, even for subgroups of young women and patients with human epidermal receptor 2‐positive breast cancer, triple‐negative breast cancer, or stage IIB disease.